The Use Of Technology In Innovation Management (Comparing The Use Of Information And Communication Technology In Innovation Management In Islamic Education Institutions And Assessing The Impact And Benefits Of Using Technology In Improving The Efficiency) - Hadi, Muh Sufyan (Review: Journal of Multidisciplinary in Social Sciences, 2025)
This study aims to compare the use of information and communication technology (ICT) in innovation management in Islamic educational institutions. This study also evaluates the impact and benefits of technology use in improving efficiency, quality, and accessibility of Islamic education. This qualitative research aims to understand the use of ICT in innovation management in Islamic educational institutions and to evaluate the impact and benefits of technology use in improving efficiency, quality, and accessibility of Islamic education. The results of this study indicate that the use of ICT can improve the efficiency and quality of Islamic education, as well as increase accessibility for students. However, this study also found that there are still some challenges in implementing ICT in Islamic educational institutions. This study implies the importance of developing effective strategies for integrating ICT into innovation management in Islamic educational institutions.